Responses of broilers to Aloe vera bioactives as feed additive: The effect of different forms and levels of bioactives on performances of broilers - Sinurat, A.P; Purwadaria, T; Togatorop, M.H; Pasaribu, T; Bintang, I.A.K; Sitompul, S; Rosida, J (Indonesian Animal Sciences Society, 2002)
Feed additives are commonly used in poultry feed as growth promotors or to improve feed efficiency. Previous results showed that Aloe vera bioactives could improve feed efficiency in broilers. Therefore, a further study was designed in order to obtain optimum doses and application methods of bioactives for broiler chickens. Aloe vera was prepared in different forms (fresh gel, dry gel, fresh whole leaf or dry whole leaf). The aloe was supplemented into the feed with concentrations of 0.25; 0.5 and 1 g/kg (equal to dry gel). Standard diets with or without antibiotics were also included as control. The diets were fed to broilers from day old to 5 weeks and the performances were observed. Results showed that the aloe-bioactives did not significantly (P>0.05) affect final body weight of broilers as compared with the control. Supplementation of 0.25 g/kg fresh gel, 0.25 and 1.0 g/kg dry gel significantly improved feed convertion by 4.7; 4.8 and 8.2%, respectively as compared with the control. This improvement was a result of reduction in feed intake or dry matter intake without reducing the weight gain. However, supplementation of whole aloe leafs could not improve feed convertion in boilers. It is concluded that the bioactives of Aloe vera could be used as feed supplement to improve feed efficiency in broilers with no deleterious effect on weight gain, carcass yield, abdominal fat levels and internal organs. The effective concentrations of aloe gell as a feed supplement based on dry matter convertion were from 0.25 g/kg fresh gel, 0.25 and 1.0 g/kg dry gel. Â Key words: Broilers, feed efficiency, feed additives, Aloe vera